Investigating the relationship of social cognitive factors and knowledge sharing behavior in teachers' virtual communities / Azura Awang - Awang, Azura (2017)
Knowledge sharing between teachers in virtual communities (VC) has been affirmed to develop teachers' professionalism in this 21st century. Knowledge is an asset in every teacher, thus, teacher hardly wants to share with others especially in VC. Hence, the objective of this study was to identify the level of Self-Efficacy, Personal Outcome Expectation, Community-Related Outcome Expectation, Trust and Knowledge Sharing Behavior among the teacher in VC and to examine the relationship of Self-Efficacy, Personal Outcome Expectation, Community-Related Outcome Expectation and Trust with Knowledge Sharing Behavior in teachers' VC in Malaysia. A total of 1431 valid responses gathered from online web survey were analyzed by using SPSS. The findings revealed that teachers were positive towards knowledge sharing behavior in VC and the predictor of knowledge sharing behavior in teachers' VC was Self-Efficacy, Trust, and Personal Outcome Expectation whilst Community-Related Outcome Expectation did not. Findings from this study contribute to the Information Technology (IT) fields by providing insights into the design and development of Knowledge Management (KM) systems; promoting teachers' perception on the importance of knowledge sharing behavior; provides new theoretical insights and also expanding the value in knowledge sharing practices in education field specifically in Malaysia. The limitations of this study were it was a cross sectional study and unable to generalize the findings to larger population. It is recommended for future works to apply mixed method and content analysis techniques to provide a deeper understanding of knowledge sharing behavior and the type of content teacher shared in VC.